Analisis Fundamental Makro, Struktur Aset Terhadap Nilai Perusahaan dengan Struktur Modal, Kinerja Keuangan, Opini Auditor sebagai Variabel Intervening pada Perusahaan Sektor Food & Beverage yang Terdaftar di BEI Periode 2016-2021 - Sari, Chindy Manika; Hwihanus (LANCAH: Jurnal Inovasi dan Tren, 2024)
The study aims to analyze the fundamental influence of macro, asset structure, capital structure, financial performance, and auditor opinion on the value of the company by considering the role of intervening variables on F&B sector companies listed in the EIB period 2016-2021. The data used is secondary data obtained from the company's (Annual Report) using the Smart-PLS 4.0 program. The results of the research show that the fundamental macro and asset structure influences insignificantly on the value of the company by considering the role of the intervening variables. Capital structures mediate the fundamental macro influence on the company's value, while financial performance mediates the influence of the asset structure on the corporate value. The auditor's opinion does not mediate the fundamental influence of macro and asset structures on the value of the company. This research provides important implications for investors, creditors, and other parties in making decisions related to investment, financing, and company valuation.